PENGARUH PROMOSI ONLINE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ONLINE ZALORA (STUDI KASUS PADA MAHASISWA INSTITUT STIAMI KAMPUS BEKASI - Irfan Setiawan; Rizki Fadillah (JAMBIS : Jurnal Administrasi Bisnis, 2023)
The study aimed to investigate and analyze the effect of online promotion and price on buying decision on Zalora online store. The research method used was quantitative method. The data sampling technique used was questionnaire. The research population was the students of Institut STIAMI Kampus Bekasi Batch 2016. The sampling technique of the study was probability sampling with simple random sampling method. There were 63 samples. The study used analysis technique of multiple linear regression estimated using software SPSS version 24. The result of the study showed that online promotion and price had positive effect on buying decision. The price variable had the most significant effect and the online promotion variable had the smallest effect. The result of t-test showed that each independent variable had significant and positive effect on buying decision. The equation model had F value of 47.462 with significance level 0.000. The result of determination coefficient analysis showed that online promotion and price only explained 61.2% effect on buying decision. While the remaining 38.8% was explained by other variables not explained in the study